ANALYSIS OF INHIBITING FACTORS, COMPARATIVE PATTERNS, AND METHODOLOGICAL GAPS OF LACK OF INTEREST IN ENGLISH PROGRAM: SYSTEMATIC LITERATURE REVIEW - Ridianto Ridianto; Riyadi Saputra; Multi Efrini; Roza Susanti; Desfi Yenti; Muhammad Yazid Fakhri (ELP (Journal of English Language Pedagogy), 2026)
This study aims to identify the dominant factors inhibiting prospective students' interest in an English Program, compare this pattern of low interest with other study programs, and uncover theoretical and methodological gaps in measuring the construct of "lack of interest." A systematic literature review (SLR) following the PRISMA 2020 protocol was conducted on the Scopus database, resulting in 53 primary studies from 2020–2026 that were analyzed thematically. The findings reveal four levels of inhibiting factors: individual (e.g., low self-efficacy), interpersonal (e.g., family expectations), institutional (e.g., inaccurate information), and macro-structural (e.g., negative career perceptions). The lack of interest in the English Program is unique due to a combination of low perceived economic value, gender stereotypes affecting both genders, and a higher perceived technological threat compared to STEM, economics, or health programs. A major gap is the absence of a standardized instrument that measures "lack of interest" as an independent construct. The study concludes that "major avoidance" deserves more scholarly attention, and recommends developing a dedicated instrument and conducting further cross-contextual empirical research.